DIGITAL COMPLEXITY IN DESTINATION BRANDING: A PRELIMINARY ANALYSIS TO DESTINATION PORTUGAL - OLIVEIRA, Eduardo (Journal of Environmental Management and Tourism, 2016)
Tourist destinations demand strategic thinking and dynamic instruments, methods and tool to address the contemporary digital complexity. The application of information communication technologies by tourism destinations, when correctly articulated with a destination branding strategy, could be a driving force to improve their strategic positioning, and enhance competitiveness. In addition, reinforce perceived images and to optimize the benefits they derive from tourism. Tourism is an important and dynamic sector in the economy of destinations. Our aim is to reinforce tourism as necessary for an economic and social transformation and as a response to the contemporary challenges. The novelty of this preliminary analysis lies in the strategic approach to the digital complexity in destination branding by researching developments in branding Portugal as a tourism destination. In terms of methodology, a brief content analysis, complemented with a text mining study, were developed. Perceive how online tourism-oriented promotional channels characterize Portugal as destination, and further discuss the best branding strategies, is a central element along the article.
Keywords: content analysis; destination branding; digital complexity; Portugal; strategy; text mining